Jugular Vein Catheter Design and Cocaine Self-Administration Using Mice: A Comprehensive Method - Valles, Gia; Huebschman, Jessica L.; Chow, Elsbeth; Kelly, Corinne; Guo, Yuhong; Smith, Laura N. (Frontiers in Behavioral Neuroscience, 2022)
Intravenous self-administration (IVSA) is a behavioral method of voluntary drug intake in animal models which is used to study the reinforcing effects of drugs of abuse. It is considered to have greater face validity in the study of substance use and abuse than other assays, and thus, allows for valuable insight into the neurobiological basis of addiction, and the development of substance abuse disorders. The technique typically involves surgically inserting a catheter into the jugular vein, which enables the infusion of drug solution after the performance of a desired operant behavior. Two nose- poke ports or levers are offered as manipulanda and are randomly assigned as active (reinforced) or inactive (non-reinforced) to allow for the examination of discrimination in the assessment of learning. Here, we describe our methodological approach to this assay in a mouse model, including construction and surgical implantation of a jugular vein catheter, set up of operant chambers, and considerations during each phase of the operant task.